PMO Dual-Track Mechanism: From Delivery Execution to Strategic Value Creation - Alin Veronika; Yusuf Latief; Leni Sagita Riantini (Journal of Project Management Research, 2025)
Project Management Offices (PMOs) have become a central organisational function for managing projects, programmes, and portfolios. Despite widespread adoption, many PMOs continue to struggle in demonstrating sustained value and strategic relevance. This white paper introduces the PMO Dual-Track Mechanism, a novel, empirically grounded model that explains how PMO performance is generated through two distinct yet interconnected pathways: Execution Track — focused on operational delivery excellence Value Track — focused on strategic alignment and value creation These two tracks are not independent. They are integrated through a critical mediating mechanism: PMO Transformation, which enables the transition from operational efficiency to strategic contribution. The model demonstrates that: Operational capabilities drive direct performance outcomes Strategic capabilities drive indirect performance outcomes through transformation PMO effectiveness emerges from the balance and interaction of both tracks This mechanism provides a new lens for understanding PMO performance, repositioning PMOs from administrative entities to adaptive governance systems and strategic value enablers.